DAMPAK BERBAGAI ALTERNATIF KEBIJAKAN TERHADAP ARUS PERDAGANGAN LADA PUTIH INDONESIA DI PASAR IMPOR LADA PUTIH DUNIA - EDIZAL - (SOCA: Jurnal Sosial Ekonomi Pertanian, 2008)
The main objective of this study are the simulation of shifter exogenous variable aschanging of demand, price and supply for performance of Indonesian white pepper trading inimport market world white pepper. The results of simulation indicate that Singapore ishighest responsive to increase demand of Indonesian white pepper, but not followed by priceresponse if increasing 5% demand world white pepper. Increasing of Indonesian whitepepper supply 5% to have influence on decreasing 2.4% of price world white pepper.Decreasing import tariff 3% white pepper for Japan and ROW more advantage for Indonesiathan decreasing import tariff the same level for USA and European Economy Community.